2007
DOI: 10.1021/bm0701604
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronic Acid Derivatives Prepared in Aqueous Media by Triazine-Activated Amidation

Abstract: A method is presented for the preparation of hyaluronic acid derivatives obtained through triazine-activated amidation. A number of amines were successfully reacted with hyaluronic acid carboxyl groups using 2-chloro-4,6-dimethoxy-1,3,5-triazine as an activating species in a mixture of water and acetonitrile under neutral conditions. By varying the amount of triazine reagent, it was possible to control the degree of modification. Depending on the amine chosen, degrees of modification ranging from 3 to 20% were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 64 publications
(36 citation statements)
references
References 15 publications
0
35
0
1
Order By: Relevance
“…The preparation of HA functionalized superparamagnetic iron oxide NPs (HA-SPIONs) started from the amine containing SPION 36 by conjugating low molecular weight HA polymer (31 kDa) using 2-chloro-4,6-dimethoxy-1,3,5-triazine (CDMT) 37 as the coupling reagent (Figure 1). The HA-SPION was thoroughly characterized by a variety of techniques including TEM, DLS, zeta potential, TGA and HRMAS-NMR (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…The preparation of HA functionalized superparamagnetic iron oxide NPs (HA-SPIONs) started from the amine containing SPION 36 by conjugating low molecular weight HA polymer (31 kDa) using 2-chloro-4,6-dimethoxy-1,3,5-triazine (CDMT) 37 as the coupling reagent (Figure 1). The HA-SPION was thoroughly characterized by a variety of techniques including TEM, DLS, zeta potential, TGA and HRMAS-NMR (Figure S1).…”
Section: Resultsmentioning
confidence: 99%
“…62, 63 Naturally existing HA has molecular weight ranging from 10 kDa to 10 MDa depending on its source and purification procedures. 28 CD44 contains a single HA binding domain, which can accommodate a HA oligosaccharide up to hexasaccharide in length.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the associative properties of these HA derivatives were found to be controlled by the complex balance between electrostatic repulsions and hydrophobic attractions associated with intra and interchain hydrogen bond interactions (Creuzet et al, 2006). Bergman et al reported the grafting of a series of amines including propylamine to HA using triazine-based activation chemistry (Bergman, Elvingson, Hilborn, Svensk & Bowden, 2007), however the rheological properties were not analysed.…”
Section: Tablementioning
confidence: 99%